A proposal of community-based firefighting in peat hydrological unit of Kahayan – Sebangau River: methods and approaches - Yulianti, N.; Kusin, K.; Jagau, Y.; Naito, D.; Susetyo, K.E. (IOP Publishing, 2020)
In 2019, Indonesia has experienced a very recent El Nino event, which generates an impact on the severity of forest and peatland fires both in Kalimantan and Sumatra. Some provinces such as Central Kalimantan, South Kalimantan, Riau, South Sumatra, and Jambi have been covered in a thick and poisonous haze for months. The total number of fire in Central Kalimantan processed from NASA hotspot data from January to October is reaches 10 000, which approximately 86% occur during two months of the dry season (September – October 2019). The areas that experienced very severe fires in 2019 were Peat Hydrological Unit (PHU) Kahayan – Sebangau River in the administrative boundaries of Pulang Pisau and Palangka Raya. The interesting is the fire in 2019 becomes the four of top fire in Central Kalimantan after 2015, 2006 and 2009. About 10,000 hectares of land including peatlands have been burned only in Central Kalimantan during the forest and land fires season. The smoldering type of peat combustion underground with low-temperature combustion is the most common occurrence in dry peatland areas. This unique fire behavior answers some of the questions why smoldering fires occur over long durations, and why peat fires are difficult to extinguish and produce more smoke. This paper will review the update of 2019’s fire in Central Kalimantan and introduce the methods and approaches of firefighting by the local community. The method that will be presented is a combination of scientific data with the experience of the firefighting team, which is called Tim Serbu Api Kelurahan (TSAK). The collaboration project between the University of Palangka Raya, Kyoto University and CIFOR that supported by the Ministry of Agriculture, Forestry and Fishery Japan has proposed to draft a manual for fire prevention and protection for the local fire fighting. This manual covers the method of fire investigation, firefighting preparedness such as making wellbore, fire break, the installation on machine and horse as well as the effective peat rewetting and watering. This method has been tested successfully to slow the movement and spread of fire under thick peat. On the other hand, there is still a need for sophisticated equipment for underground fire detection such as thermal cameras or drones.